2010
DOI: 10.1056/nejmoa0911123
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GD2 Antibody with GM-CSF, Interleukin-2, and Isotretinoin for Neuroblastoma

Abstract: BACKGROUND Preclinical and preliminary clinical data indicate that ch14.18, a monoclonal antibody against the tumor-associated disialoganglioside GD2, has activity against neuroblastoma and that such activity is enhanced when ch14.18 is combined with granulocyte–macrophage colony-stimulating factor (GM-CSF) or interleukin-2. We conducted a study to determine whether adding ch14.18, GM-CSF, and interleukin-2 to standard isotretinoin therapy after intensive multimodal therapy would improve outcomes in high-risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
1,683
4
22

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 1,534 publications
(1,739 citation statements)
references
References 31 publications
30
1,683
4
22
Order By: Relevance
“…Recently, it has been reported that the addition of the anti-GD2 antibody ch14.18/SP2/0, combined with rIL-2 and GM-CSF, to standard therapy provides a clinical benefit with a 20% improvement in the 2-year prevention of relapse for children with high-risk neuroblastoma [52]. The primary mechanism of action of the anti-GD2 antibody is the induction of ADCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that the addition of the anti-GD2 antibody ch14.18/SP2/0, combined with rIL-2 and GM-CSF, to standard therapy provides a clinical benefit with a 20% improvement in the 2-year prevention of relapse for children with high-risk neuroblastoma [52]. The primary mechanism of action of the anti-GD2 antibody is the induction of ADCC.…”
Section: Discussionmentioning
confidence: 99%
“…The GD2-specific chimeric antibody ch14.18 generated in SP2/0 hybridoma cells Overall survival at two years was 86% for the immunotherapy group versus 75% for the standard treatment group (p= 0.016) [52]. It has been shown for the first time that the inclusion of immunotherapy in standard therapy provides a clinical benefit with improved event-free and overall survival for children with high-risk neuroblastoma, highlighting the role of immunotherapy in treatment of this challenging disease.…”
Section: Gd2 and Anti-gd2 Antibody Immunotherapymentioning
confidence: 99%
“…The only clinically available mAbs in neuroblastoma cells is dinutuximab, a chimeric, human-murine, anti-disialoganglioside GD2 overexpressed on NB tumors. Dinutuximab was approved in combination with granulocyte/monocyte-colony stimulating factor (GM-CSF), aldesleukin (interleukin-2 [IL-2]), and isotretinoin (13-cis-retinoic acid [RA]) for maintenance treatment of patients with high-risk neuroblastoma who respond at least to firstline multimodality therapy [10]. In phase III trials, dinutuximab increased 2-year event-free survival (EFS) and overall survival (OS) compared to standard treatment.…”
Section: Immunotherapy Of Neuroblastomamentioning
confidence: 99%
“…Their homing in tumor microenvironment site and production of vEGF contribute to metastasis [42]. In aggressive NMA neuroblastoma, it was shown that TAMs are correlated to bad prognosis [10]. Macrophages are key players in maintaining the tissue homeostasis, shaping adaptive immune response, inflammation, and tissue repair [44].…”
Section: Twist1 Myc and Immune Systemmentioning
confidence: 99%
“…5). 36 A study gathering further information to support a licensing application is in progress. Recent reanalysis of a German study nonrandomly assigning patients to ch14.18 after high-dose therapy supports its efficacy.…”
Section: Antiangiogenesismentioning
confidence: 99%